A percepção espacial de pessoas com deficiência visual: estudo de caso em ambientes de restaurantes em João Pessoa-PB - Santos, Mariana de Sousa Siqueira (2015)
In the cities predominate information and visual references. People with visual impairment have a different environmental perception of the sighted ones, because of their visual impairment, forcing them to use other senses. These people have their impaired autonomy in certain areas where is no implementation of accessibility requirements to facilitate their orientation and spatial perception. This thesis discusses to which extent the common meeting places of citizens, especially restaurants, considering the specific needs of people with visual impairment. Thus, the general goal of this research is to identify and understand how is the perception and physical-spatial orientation of visually impaired people in the built environment, considering different physical-spatial contexts, taking as object of study restaurants located in the city João Pessoa, Paraíba. The methodological course is characterized by multimethod approach and is divided into two stages: literature and field research, which involves the application of methods, like Walkthrough, Accompanied Walk and Wish Poem, in order to collect data, trying to understand the dynamics of the restaurants, the physical and spatial orientation of blind and low vision people and how they idealize these restaurants. At the time this research began, it was conducted at the Institute of the Blind, a 20-day immersion in rehabilitation programs: Daily Life Activities and Orientation and Mobility to know the techniques that the visually impaired learn on their day by day basis. The results of Accompanied Walks indicated that all participants with visual impairment had difficulties related to spatial orientation of the four spatial accessibility components. It was concluded then that analyzed restaurants showed inefficient space readability and scarce means which would contribute to the perception and spatial orientation of blind and low vision. In poems produced by these participants, it was observed that they idealize a space that provides accessible resources to enable them to carry out activities in restaurants areas with autonomy and safety. By reflecting upon the issue, we expect to make not only the designers sensible, but also the commercial sector, particularly the food industry, that they can take measures to promote the spatial accessibility for people with visual disabilities.